The school portfolio (II) (Journal of Parents and Teachers, 2014)
This last presentation of the miniseries “The teacher’s portfolio” guides teachers about the electronic and paper format, explaining in a chart the advantages and disadvantages of both formats. Regarding the content of the portfolio, this must include: pedagogic materials, evaluation tools, students work, learning activities, participation in school meetings and school commissions and also personal reflections.
Keywords: school portfolio; professional training; planning; orientation; format; content